Peer Support for Type 2 Diabetes Management in Low- and Middle-Income Countries (LMICs): A Scoping Review - Diana Sherifali; Lilian Pinto da Silva; Pooja Dewan; F. Aaysha Cader; Zainab Dakhil; Bishal Gyawali; Sheila Klassen; Israa Fadhil Yaseen; Milos Jovkovic; Saira Khalid; Donna Fitzpatrick-Lewis; Paige Alliston; et al. (Ubiquity Press, 2024)
Background: Although there is evidence of peer support in high-income countries, the use of peer support as an intervention for cardiometabolic disease management, including type 2 diabetes (T2DM), in low- and middle-income countries (LMICs), is unclear. Methods: A scoping review methodology was used to search the databases MEDLINE, Embase, Emcare, PsycINFO, LILACS, CDSR, and CENTRAL. Results: Twenty-eight studies were included in this scoping review. Of these, 67% were developed in Asia, 22% in Africa, and 11% in the Americas. The definition of peer support varied; however, peer support offered a social and emotional dimension to help individuals cope with negative emotions and barriers while promoting disease management. Conclusions: Findings from this scopingreview highlight a lack of consistency in defining peer support as a component of CMD management in LMICs. A clear definition of peer support and ongoing program evaluation is recommended for future research.